Friday, 15 June 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.4495
|View full text |Cite
|
Sign up to set email alerts
|

FRI0520 Discovery of potential biomarkers for the diagnosis of erosive and nodal hand osteoarthritis

Abstract: BackgroundTwo different phenotypes of hand osteoarthritis (HOA) have been defined: nodal hand osteoarthritis (NHOA) and erosive hand osteoarthritis (EHOA). NHOA involve bone enlargement of the underlying interphalangeal joints, which may typically give rise to Heberden’s nodes, synovitis and swelling. EHOA is a particularly aggressive form characterised by an abrupt onset, as well as signs of inflammation and subchondral erosions. In the absence of efficient diagnostic methods, searching for specific biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…Ranges in RV1 to RV4 are significantly different, in accordance with previous studies that found that AROM is reduced in joints affected by HOA [10][11][12] and that the range of motion used in compromised joints is also reduced in certain activities of daily living [11,16,17]. In this study, the ranges used by patients are significantly lower for finger arch coordination, thumb-index pinch, and forced thumb opposition, and they are consistent with limitations in compromised joints (finger PIP joints and thumb joints [47,49]). However, patients present a higher range in hand closure, although with a median hand closure that is less closed (or flexed).…”
Section: Discussionsupporting
confidence: 90%
“…Ranges in RV1 to RV4 are significantly different, in accordance with previous studies that found that AROM is reduced in joints affected by HOA [10][11][12] and that the range of motion used in compromised joints is also reduced in certain activities of daily living [11,16,17]. In this study, the ranges used by patients are significantly lower for finger arch coordination, thumb-index pinch, and forced thumb opposition, and they are consistent with limitations in compromised joints (finger PIP joints and thumb joints [47,49]). However, patients present a higher range in hand closure, although with a median hand closure that is less closed (or flexed).…”
Section: Discussionsupporting
confidence: 90%
“…Palm arch FE 28 ( 9) 19 ( 7) 17 ( 11) 36 (8) 21 ( 16) 18 ( 6) 10 ( 16) 28 ( 16) 11) 10 ( 6) 59 (9) 30 ( 10) 45 ( 12) 8 ( 11) 52 (13) Little FE 32 ( 9) 52 ( 12) 8 ( 11) 60 ( 12) 36 ( 13) 47 ( 14) 14 ( 14) 60 (15) Index PIP FE 38 (10) 50 ( 13) 17 ( 11) 67 ( 12) 39 ( 12) 46 ( 13) 17 ( 11) 63 ( 14) Middle FE 38 (10) 46 ( 12) 17 ( 14) 63 ( 8) 39 ( 10) 42 ( 11) 17 (10) 59 (11) Ring FE 43 ( 10) 50 ( 14) 19 ( 15) 69 ( 9) 44 ( 11) 45 ( 17) 17 ( 10) 63 ( 14)…”
Section: Discussionunclassified
“…Compromise of the PIP and DIP joints commonly displays bone enlargement at the joints, producing rejection and a disability that is more perceived than real [15]. Despite its high prevalence, HOA is a silent degenerating disorder that is clinically disregarded in most cases, except in very severe situations.…”
Section: Introductionmentioning
confidence: 99%